The Influence of Job Stress and Psychosocial Factors on Employee Performance through Leadership Quality - Afifah, Zumrotin Nur; Kurniasih, Dewi; Rachman, Farizi (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2024)
The development of Indonesia's industry is currently changing from commodity-based to manufacture-based. The manufacturing industry cannot be separated from the role of the packaging industry. So it is necessary to have Human Resources with good performance to be able to help achieve the goals and vision and mission of the company. Employee performance comes from two factors, namely individual factors and organizational environmental factors. The purpose of this study was to determine the effect of work stress and psychosocial factors consisting of job demands and work organization on employee performance in packaging companies through leadership quality. The method used is PLS-SEM with a sample of 75 people. The results showed that work stress had a significant effect on employee performance (p-value = 0.000), job demands and work organization had no significant effect on employee performance (p-value = 0.501 on job demands and p-value = 0.658 on work organization) , leadership quality has no significant effect on employee performance (p-value = 0.685), work stress has no significant effect on employee performance through leadership quality (p-value = 0.740), and job demands and work organization have no significant effect on employee performance through quality leadership (p-value=0.877 on job demands and p-value=0.725 on work organization). While the r-square value which shows the influence of work stress variables, job demands, work organization, and leadership quality on employee performance is 63.7%.